Public and Special Education Teachers Attitudes Toward Behavior Modification (Journal of the College of Basic Education, 2022)
This Study aimed to examine the attitudes of public and special education teachers toward behavior modification .The Study population consisted of (182) teachers in Amman and Al-salt . A questionnaire for attitudes was built and applied, after its validity and reliability were verified, to public and special education teachers . T test was usedThe Study revealed the following results:Both of public and special education teachers have appositive attitudes toward behavior modification.There are significant differences on the attitudes of teachers according to gender , specialization , behavior modification course in behalf of men teachers , special education teachers , teachers who took a course in behavior modification .